The Influence of Job Satisfaction and Career Satisfaction on Turnover Intention with Organizational Commitment as a Mediating Variable: A Case Study at PT X Manufacturing Company, Plant 1 - Samsul Kosasi; Nina Nurani (Dinasti International Journal of Education Management and Social Science, 2025)
This study aims to analyze the influence of job satisfaction and career satisfaction on turnover intention, with organizational commitment as a mediating variable. The study was conducted at PT X, a manufacturing company located in Karawang. The research approach used was quantitative with descriptive and verificative methods. The study sample used the Slovin formula through Proportionate Stratified Random Sampling, and data were collected through interviews and questionnaires. Data analysis was performed using multiple linear regression and path analysis using SPSS 26. The results showed that, partially, job satisfaction and career satisfaction significantly influenced turnover intention and organizational commitment. Organizational commitment significantly influenced turnover intention. Organizational commitment did not significantly mediate the effect of job satisfaction on turnover intention, but significantly mediated the effect of career satisfaction on turnover intention.